Analisis Perlindungan Hukum Dalam Perspektif Hukum Ekonomi Syariah Terhadap Konsumen Gadai Emas di Pegadaian Syariah Centeral Makassar - Wahyudi, Audra Anandira; H, Hasibuddin; Lawang, Hasanna (Media Hukum Indonesia (MHI), 2025)
This study aims to analyze the form and effectiveness of legal protection for consumers in Islamic gold pawn transactions at Pegadaian Syariah Centeral Makassar from the perspective of Islamic Economic Law. Legal protection in Islamic financial transactions is essential to ensure justice, transparency, and the protection of consumer rights in accordance with Sharia principles. This research employs a descriptive qualitative approach using data collection techniques such as in-depth interviews, observation, and documentation. The findings indicate that Pegadaian Syariah Centeral Makassar has implemented the rahn contract in accordance with Sharia, provided transparent information to consumers, and safeguarded consumer rights regarding pledged goods fairly. However, challenges remain, including limited consumer understanding of their rights and suboptimal dispute resolution mechanisms. The study concludes that while Pegadaian Syariah generally complies with Sharia-based consumer protection principles, there is a need to improve public education and strengthen Sharia-based regulations and dispute resolution institutions at the local level. These findings are expected to contribute to the development of consumer legal protection in Indonesia's Islamic finance sector.